The Nature of a House Building a World that Works - Woodwell, George M.; SpringerLink (Online service) (Washington, DC : Island Press/Center for Resource Economics : Imprint: Island Press, 2012)
In this candid and informative book, George M. Woodwell, a leader in the study of global environmental change, illuminates practical considerations (and frustrations) involved in (3z(Bbuilding green.(3y (BWhen the renowned Woods Hole Research Center needed a new office, Woodwell led efforts to utilize (3z(Bstate-of-the-shell(3y (Bgreen building techniques to retrofit a Victorian mansion built in 1877 into the Center$1 (Bs new home. This is the story of how scientists and contractors alike confronted the limitations of available materials, laws, and building codes. Woodwell sets this struggle in a larger context, as part of the global need to minimize carbon emissions and environmental impacts. Beginning with his experience of the retrofit of a single building, he shares insights into rethinking how we design, use, and adapt the built environment to preserve the functional integrity of the natural landscape.s
Foreword -- Acknowledgements -- Preface: A Small Matter of Habitat and Housing -- 1. Building a World that Works -- 2. Back to the Beginning: The Woods Hole Research Center -- 3. Redesigning Hilltop House: Triumphs and Compromises -- 4. Energy in a New World -- 5. Materials, Sewage, and Costs: Adjusting Our Vision -- 6. The Product: A Campus that Works . . . And a World that Might -- Notes -- Index.
Keywords: Environmental sciences; Architecture; Environmental law; Environment; Environmental Law/Policy/Ecojustice.; Architecture, general; Energy Efficiency (incl. Buildings).; Fossil Fuels (incl. Carbon Capture).; Basics of Construction